2023
DOI: 10.1363/psrh.12220
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of COVID‐19‐related changes in abortion service availability and use in Washington, DC, Maryland, and Virginia

Abstract: Objectives This exploratory study aimed to assess COVID‐19‐related changes in abortion service availability and use in Washington, DC, Maryland, and Virginia. Design Data came from a convenience sample of eight abortion clinics in this region. We implemented a cross‐sectional survey and collected retrospective aggregate monthly abortion data overall and by facility type, abortion type, and patient characteristics for March 2019–August 2020. We evaluated changes in the distribution of the total number of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Despite abortion's legality prior to the COVID‐19 pandemic, numerous barriers already constrained abortion care in the US: unaffordable out‐of‐pocket procedural costs due to insurance coverage prohibitions, scarcity of abortion providers, difficulty finding transportation to clinics in distant locations, internalized and externalized stigma, and legislative restrictions requiring mandatory waiting periods and other delays in care 11,23,24 . Our study adds to a growing body of literature documenting the broad impacts of COVID‐19 on people trying to seek abortion services 1,4,10,25–29 . Findings from this study document that the COVID‐19 pandemic both amplified pre‐existing obstacles to abortion care and added new challenges.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Despite abortion's legality prior to the COVID‐19 pandemic, numerous barriers already constrained abortion care in the US: unaffordable out‐of‐pocket procedural costs due to insurance coverage prohibitions, scarcity of abortion providers, difficulty finding transportation to clinics in distant locations, internalized and externalized stigma, and legislative restrictions requiring mandatory waiting periods and other delays in care 11,23,24 . Our study adds to a growing body of literature documenting the broad impacts of COVID‐19 on people trying to seek abortion services 1,4,10,25–29 . Findings from this study document that the COVID‐19 pandemic both amplified pre‐existing obstacles to abortion care and added new challenges.…”
Section: Discussionmentioning
confidence: 74%
“…11,23,24 Our study adds to a growing body of literature documenting the broad impacts of COVID-19 on people trying to seek abortion services. 1,4,10,[25][26][27][28][29] Findings from this study document that the COVID-19 pandemic both amplified pre-existing obstacles to abortion care and added new challenges. Research has demonstrated system-level abortion clinic closures and protocol modifications occurred during the early phase of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our findings of increased use of medication abortion during the pandemic echo those of other studies. [12][13][14][15][16][56][57][58] Notably, this shift in method is not exclusive to states that restricted abortion during the pandemic, suggesting that the additional hyper-surveillance and regulation of facilities in states like Kentucky, Ohio, and West Virginia was likely not a singular driving factor in this shift to increased medication abortion use. Rather, facilities in these states adapted their service delivery in part based on public health guidance.…”
Section: Discussionmentioning
confidence: 99%
“…In Texas, which banned instrumentation abortions under state emergency COVID orders, there was increased use of medication abortion in the first trimester 14 . Facilities in Maryland, Virginia, the District of Columbia, 15 and Southern California 16 also experienced increases in medication abortion provision during the pandemic, despite a lack of state orders requiring them to do so. Contrastingly, facilities in Northern California 17 saw an increase in the number of instrumentation abortions during this same period, suggesting variation within individual state contexts.…”
Section: Introductionmentioning
confidence: 99%